Questioning the Domain of the Business Ethics Curriculum - Crane, Andrew (Journal of business ethics, 2004)
This paper reassesses the domain of the business ethics curriculum and, drawing on recent shifts in the business environment, maps out some suggestions for extending the core ground of the discipline. It starts by assessing the key elements of the dominant English- language business ethics textbooks and identifying the domain as reflected by those publications as ‘where the law ends’ and ‘beyond the legal minimum’. Based on this, the paper identifies potential gaps and new areas for the discipline by drawing on four main aspects. First, it argues that the domain of business ethics requires extensions dependent on the particular geographic region where the subject is taught. A second factor for broadening the scope is the impact of recent scandals, which arguably direct the focus of ethical inquiry towards the nature of the business systems in which individuals and corporations operate. Third, the impact of globalization and its result on growing corporate involvement in regulatory processes is discussed. Fourth and finally, business ethics reaches beyond the traditional constituencies of ‘economic stakeholders’ as new actors from civil society enter the stage of ethical decision making in business. We conclude by suggesting that a reconsideration of the domain of business ethics, especially in Europe, is timely, but that to do so represents a major challenge to business ethics educators.